HUBUNGAN KEPERCAYAAN DIRI DAN KETERBUKAAN DIRI DENGAN KOMPETENSI KOMUNIKASI SISWA DI SMPN 12 PURWOREJO - Afidati Hidayanti, Syafira; Noor Rakhmad, wiwid; Sunarto, Sunarto (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
Some students at SMPN 12 Purworejo are known to have less than optimal communication competence. Students experience difficulties in communication situations in the classroom which is indicated by difficulty in expressing opinions, less active in discussion sessions, and difficulty answering questions. This causes the teaching and learning process in schools to be less effective and the academic achievements obtained are also not optimal. The difficulties experienced by these students are influenced by self-confidence and self-disclosure. This research examines the relationship between self-confidence and self-disclosure with students' communication competence at SMPN 12 Purworejo. This research uses a positivism paradigm and a quantitative approach. Data were collected by distributing questionnaires to 100 respondents with the characteristics of teenagers aged 12-15 years, male and female, and attending SMPN 12 Purworejo. The results of correlation analysis show a significant positive relationship between self-confidence and communication competence and between self-disclosure and communication competence. This relationship is in line with the argumentativeness approach in Super Traits Theory which explains that individuals who have argumentative skills are individuals who are competent in arguing, where individual communication competence includes self-confidence and self-openness (Littlejohn, Foss, Oetzel, 2017). The results of this research indicate that students with good self-confidence and self-disclosure have good communication competence. It becomes easier for students to master the communication situations they face.